Effect of diabetic case management intervention on health service utilization in Korea. Issue 6 (12th May 2014) - Shin, Soon Ae; Kim, Hyeongsu; Lee, Kunsei; Lin, Vivian; Liu, George
Abstract : This study is to estimate the effectiveness of a diabetic case management programme on health‐care service utilization. The study population included 6007 as the intervention group and 956 766 as the control group. As the indicators of health‐care service utilization, numbers of medical ambulatory consultations, days of medication prescribed and medical expenses for one year were used, and we analysed the claim data of the health insurance from 2005 to 2007. The study population was classified into three subgroups based on the number of medical ambulatory consultations per year before this intervention. In the under‐serviced subgroup, the intervention group showed a significant increase in the number of consultations (3.2), days of prescribed medication (66.4) and medical expenses (287 900 KRW) compared with the control group. Conversely, in the over‐serviced subgroup, the intervention group showed a less decrease days of prescribed medication (1.6) compared with the control group. This showed that the case management programme led the intervention group to optimize their utilization of health‐care services by subgroups. It is necessary to evaluate the appropriateness of health‐care usage and clinical outcome to show the direct effectiveness of the case management programme by subgroups.